STUDI KOMUNITAS RUMPUT LAUT DI PANTAI SANUR DAN PANTAI SAWANGAN NUSA DUA BALI - GALIH INDRAWATI; I WAYAN ARTHANA; I NYOMAN MERIT (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Aims of this research are to analyze structure community population, relative population, variety domination, heterogeneous, and equality of seaweed species in Sanur and Sawangan Beach Nusa Dua.The result of the study shows that in Sanur and Sawangan Beach observed 13 related seaweed species were observed, which are: Ulva reticulata, Chaetomorpha crassa, Bornetella nitida, Halimeda macroloba, Padina australis, Sargassum binderi, Hypnea asperi, Dictyopteris sp, Gracilaria coronapifolia, Gracilaria gracilis, Acanthopora spicifera, Euchema edule, Euchema denticulatum Meanwhile, , Caulerpa racemosa, Boergesiana forbessii, Sargassum crassifolium, Gelidium sp, Turbinaria ornata, Gracilaria foliifera only observed in Sanur Beach and species of Actinotrichia fragilis, Ulva lactuca, Euchema serra, Turbinaria conoides observed in Sawangan Beach, Nusa Dua.Heterogeneous value index (H) in Sanur Beach is 0.75 – 1.87 categorized as medium category, except in station five characterized as low category. Domination index (C) is 0.10 – 0.28, where there is no dominated species. Equality index value (E) is 0.32 – 0.85 in unstable condition, except in station one is stable. In Sawangan Beach, heterogeneous indexes is 1.04 – 1.54, that spread in all stations by medium category. Domination index is 0.14 – 0.30, indicated that there is no dominant species. Equality index is 0.47 – 0.74, by stabile condition in station one, while others station is unstable. Highest relatif population in Sanur Beach is 37.63% in station three (Gracilaria foliifera). In Sawangan Nusa Dua Beach is Hypnea asperi (48.65%).Substrate analysis show that Sanur and Sawangan Beach has mud sand types. Water temperature in both research locations approximately is 28.90 C – 30.40 C, pH 7.00 – 7.80 and dissolved oxygen around 6.8mg/1-7.4mg/l.